Enhancing Conceptual Understanding in Junior High School Science through the POE2WE Learning Model - Faridha Noer Barkah; Aulia Novitasari; Rismala Dewi (ISEJ : Indonesian Science Education Journal, 2025)
Conceptual understanding remains a fundamental yet persistently challenging objective in junior high school science education, particularly in abstract topics such as cell structure and function. Traditional and minimally guided inquiry-based instruction has been shown to inadequately support deep conceptual processing and conceptual change. This study aimed to examine the effect of the Predict-Observe-Explain-Elaboration-Write-Evaluation (POE2WE) learning model on students’ conceptual understanding in science learning. A quantitative quasi-experimental design with a non-equivalent control group pretest–posttest structure was employed, involving 64 eighth-grade students from a public junior high school in Indonesia, divided into an experimental group taught using POE2WE and a control group receiving conventional inquiry-based instruction. Students’ conceptual understanding was measured using a validated essay-based instrument aligned with Bloom’s revised taxonomy. The results revealed that students in the POE2WE group achieved significantly higher posttest scores and greater normalized learning gains than those in the control group, with the most pronounced improvements observed at higher cognitive levels (C4-C6). These findings indicate that the integration of prediction, elaboration, reflective writing, and evaluation within POE2WE effectively facilitates deeper conceptual processing and conceptual change. The study contributes theoretically by reinforcing constructivist perspectives on structured cognitive engagement and practically by suggesting that POE2WE provides a viable instructional framework for improving conceptual understanding and addressing misconceptions in secondary science classrooms.